Mesoionic sydnone: a review in their chemical and biological properties - Abdualkader, Abdualrahman Mohammed; Bakhtiar, M. Taher; Nik Yusoff, Nik Mohd. Idris (Innovare Academic Sciences, 2017)
Various literature sources have documented sydnones as important molecules with exclusive chemical properties and a wide spectrum of bioactivities. Sydnone can be defined as a five-membered pseudo-aromatic heterocyclic molecule. Classically, 1,2,3-oxadiazole forms the main skeleton of sydnone. The molecule has delocalized balanced positive and negative charges. The five annular atoms share the positive charge and the enolate-like exocyclic oxygen atom bears the negative charge. The hydrogen atom at the position C4 was proved to have acidic and nucleophilic functionalities making the sydnone ring reactive towards electrophilic reagents. These unique chemical features enable sydnones to interact with biomolecules resulting in important therapeutic effects like anticancer, antidiabetic, antimicrobial, antioxidant and anti-inflammatory. Consequently, we aim from the current article to review the available chemical and pharmacological information on sydnone and its derivatives.